2013
DOI: 10.2166/wst.2013.550
|View full text |Cite
|
Sign up to set email alerts
|

A molecular imprinted polymer based sensor for measuring phosphate in wastewater samples

Abstract: Phosphate detection in water samples is still completed using colorimetric standard methods, which have a number of disadvantages, to such as being time consuming, requiring filtration, a number of different reagents, frequent calibration and proper disposal of waste chemicals generated. Hence, a simple cost effective analytical method and instrumentation is highly desirable to aid the optimisation of treatment processes and assist the water industry in their efforts to comply with stringent regulations such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
5
2
Order By: Relevance
“…where σ is the standard deviation got from current method used in this experiment and m is the slope of calibration line. The detection limit is 1.97 μg L −1 , which is better than the reported detection limits of 0.16 mg L −1 and 18.8 μg L −1 by Christopher 48 and Gong 49 , respectively.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…where σ is the standard deviation got from current method used in this experiment and m is the slope of calibration line. The detection limit is 1.97 μg L −1 , which is better than the reported detection limits of 0.16 mg L −1 and 18.8 μg L −1 by Christopher 48 and Gong 49 , respectively.…”
Section: Resultscontrasting
confidence: 61%
“…The detection limit is 1.97 μg L −1 , which is better than the reported detection limits of 0.16 mg L −1 and 18.8 μg L −1 by Christopher48 and Gong49, respectively.…”
Section: Resultscontrasting
confidence: 61%
“…For example, Warwick et al reported a detection system based on MIPs combined with conductometric transducer for monitoring phosphates in environmental water samples [ 35 ]. Previous studies demonstrated that N-allylthiourea was the appropriate monomer for phosphate recognition [ 36 ]. The thiourea-based MIP was first optimized in terms of the optimal cross-linking monomer and ideal ratio of functional monomer to template (phenylphosphonic acid).…”
Section: Biomimetic Approaches For Sensing Water Qualitymentioning
confidence: 99%
“…Imprinting such a template will thus result in small cavities. Therefore, it was deemed that shortest cross-linkers, such as EGDMA and bisacrylamide, would likely be more appropriate to enhance the rigidity of the polymeric matrix and uphold the integrity of the recognition sites (Warwick et al, 2014b).…”
Section: Phosphate Imprintingmentioning
confidence: 99%